2019
DOI: 10.3386/w25632
|View full text |Cite
|
Sign up to set email alerts
|

Information Source and Cigarettes: Experimental Evidence on the Messenger Effect

Abstract: for helpful feedback. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…First, our participants knew our nudges were part of a research study. However, how people respond to information depends on which entity delivers that information [18,33]. Our nudges might be more or less effective depending on how people perceive the entity administering the nudges.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…First, our participants knew our nudges were part of a research study. However, how people respond to information depends on which entity delivers that information [18,33]. Our nudges might be more or less effective depending on how people perceive the entity administering the nudges.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…A better public health strategy might focus less on the details of the messages and more on the 'messenger' or the information source. Studies in behavioural economics have shown how messengers who are authority figures, share similar characteristics with and are likable to the target individuals, tend to be more successful in getting their messages across and, in turn, change individuals' choices and behaviours (37,38). Given that part of the social-identity effects is explained by political identity, non-mask wearers might be more willing to listen to a message about face mask's effectiveness from an authoritative figure in the Republican party or non-political figures who share similar characteristics or are generally well-liked by non-mask wearers.…”
Section: Discussionmentioning
confidence: 99%
“…The second component of the analysis considers the role of messengers as moderators of the message (Druckman, 2001b). The tendency of individuals to alter how they process information based on characteristics of the person delivering the message has been widely studied in behavioral economics, psychology, and marketing (Dolan, P., Hallsworth, Halpern, King, Metcalfe, & Vlaev, 2012;Maclean, Buckell, & Marti, 2019;Kassin, 1983;Wood, Solomon, & Englis, 2005). These literatures have amassed evidence which suggests we are more likely to comply with directives when they come from authoritative sources (Hofling, C., Brotzman, Dalrymple, Graves, & Pierce, 1966), from people who are similar to us (Durantini, Marta, Dolores, Amy, Allison, & Jeffrey, 2006; Karlan & Appel, 2011), those viewed as experts (Webb & Sheeran, 2006), or messengers we find more likable (Cialdini & Cialdini, 1993).…”
Section: The Communication Frames Surrounding Social Distancingmentioning
confidence: 99%